Evidence of an epidemic spread of KPC-producing Enterobacterales in Czech hospitals - Kraftova, Lucie; Finianos, Marc; Studentova, Vendula; Chudejova, Katerina; Jakubu, Vladislav; Zemlickova, Helena; Papagiannitsis, Costas C; Bitar, Ibrahim; Hrabak, Jaroslav (Scientific reports, 2021)
The aim of the present study is to describe the ongoing spread of the KPC-producing strains, which is evolving to an epidemic in Czech hospitals. During the period of 2018-2019, a total of 108 KPC-producing Enterobacterales were recovered from 20 hospitals. Analysis of long-read sequencing data revealed the presence of several types of blaKPC-carrying plasmids; 19 out of 25 blaKPC-carrying plasmids could be assigned to R (n = 12), N (n = 5), C (n = 1) and P6 (n = 1) incompatibility (Inc) groups. Five of the remaining blaKPC-carrying plasmids were multireplicon, while one plasmid couldn't be typed. Additionally, phylogenetic analysis confirmed the spread of blaKPC-carrying plasmids among different clones of diverse Enterobacterales species. Our findings demonstrated that the increased prevalence of KPC-producing isolates was due to plasmids spreading among different species. In some districts, the local dissemination of IncR and IncN plasmids was observed. Additionally, the ongoing evolution of blaKPC-carrying plasmids, through genetic rearrangements, favours the preservation and further dissemination of these mobile genetic elements. Therefore, the situation should be monitored, and immediate infection control should be implemented in hospitals reporting KPC-producing strains.
Keywords: Epidemics; lidé; bakteriální léková rezistence; nemocnice; antibakteriální látky; Klebsiella pneumoniae; beta-laktamasy; Hospitals; beta-Lactamases; Humans; Anti-Bacterial Agents; Bacterial Proteins; Česká republika; Klebsiella Infections; Drug Resistance, Bacterial; bakteriální proteiny; Czech Republic; epidemie; infekce bakteriemi rodu Klebsiella